Analisis Pengembangan Usaha Mikro Kecil Dan Menengah (UMKM) Di Kawasan Wisata Pantai Panjang Bengkulu - Julika, Vanda ibra; Salsabilla, Lulitia Putri; Sumarni, Yenti (Pakis Journal Institute, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy, particularly in the tourism area of Pantai Panjang, Bengkulu. This study aims to analyze the factors influencing the development of MSMEs in this region, focusing on their potential, challenges, and the impact of the tourism sector on business sustainability. Using a descriptive qualitative approach, data was collected through in-depth interviews and field surveys with MSME actors, tourists, and local communities. The findings reveal that MSMEs in Pantai Panjang have significant potential, especially in the fields of culinary, souvenirs, and handicrafts. However, they face challenges such as limited managerial skills, marketing capabilities, infrastructure, and access to capital. The COVID-19 pandemic also had a substantial impact on this sector, although some MSME actors successfully adapted by utilizing digital technology. The study suggests the need for government and tourism sector support in the form of skill training, capital access, and infrastructure development to ensure the sustainability and growth of MSMEs in the Pantai Panjang tourism area.